Aquilaria malaccensis and Pandanus amaryllifolius mediated synthesis of tin oxide nanoparticles: The effect of the thermal calcination temperature. (2023) - Buniyamin, I.; Akhir, R.M.; Nurfazianawatie, M.Z.; Omar, H.; Malek, N.S.A.; Rostan, N.F.; Eswar, K.A.; Rosman, N.F.; Abdullah, M.A.; Asli, N.A.; Khusaimi, Z.; Rusop, M.
Abstract: The conventional methods to produce beneficial SnO2 Nps are tedious, expensive and harmful. Having this, the researcher has introduced a green synthesis technique that offers simplicity, non-toxic and economical techniques. In this study, the bioactive compound in A. malaccensis and P. amaryllifolius leaves was utilized to produce SnO2 Nps. The leaves extract was mixed with tin (iv) chloride pentahydrate solution, followed by a drying and calcination process ranging from 600, 700 and 800 °C. XRD results showed the impact of the temperature increment on the crystallinity characteristics, whereby the diffraction peaks were sharpened and intense as temperature arose and the average crystallite sizes of SnO2 Nps were found to be 6.3 nm and 10.5 nm from both leaves. The morphological images were spherical with regularities and tended to be grown to spherical grain when introduced to higher temperatures. UV–vis diffuse reflectance analysis revealed a higher surface-to-volume ratio and excellent light-harvesting manifested by SnO2 Nps mediated from P. amaryllifolius, resulting in 86 % of reflectance value, slightly higher than former nanoparticles that obtained 46 %. The rising temperature in the calcination led to the decrease of the energy band gap for SnO2 Nps prepared using A. malaccensis leaves extracts, as it is believed quantum size might be of influence. From the FTIR result, the drying process at 50 °C for the colloidal mixture apparently pre-calcined the solid particle, but eventually, the low temperature could not assist the nucleation of the SnO2 Nps growth. Somehow, the application of calcination temperature to the colloidal particle suppressed all the organic moiety, which furnished pure SnO2 Nps as the product. By having a good result for reflectance and band gap, the produced SnO2 Nps is best to be suggested for catalytic application, especially for water remediation.